2019
DOI: 10.1144/jgs2019-048
|View full text |Cite
|
Sign up to set email alerts
|

Weathering history and landscape evolution of Western Ghats (India) from 40 Ar/ 39 Ar dating of supergene K–Mn oxides

Abstract: Laterites preserved on both sides of the Western Ghats Escarpment of Peninsular India have formed by long-term lateritic weathering essentially after India-Seychelles continental break up following Deccan Traps emplacement (c. 63 Ma ago). Supergene manganese ores of the Western Ghats were formed on Late Archean manganese protores. Among Mn oxides composing the ores, cryptomelane (K-rich Mn oxide) was characterized and dated by 40 Ar/ 39 Ar geochronology. Measured ages complement those previously obtained in ot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(12 citation statements)
references
References 60 publications
0
10
0
Order By: Relevance
“…Likewise, thick bauxitic profiles later formed from weathering of 14 Ma to 23 Ma old trachyte and basalt are well preserved at altitudes of 1500 to 1800 m in the eastern Nigeria (Schwarz, 1997). With the mid-Miocene climatic optimum, Lateritic weathering intensified in Africa (e.g., Beauvais et al, 2008;De Putter and Ruffet, 2020), and more generally on continents of the inter-tropical belt (Retallack, 2010) even at relatively high altitudes, e.g., upon elevated continental margins (Jean et al, 2020), where transported-limited erosion regimes have potentially controlled landscapes evolution over the Cenozoic.…”
Section: Introductionmentioning
confidence: 96%
“…Likewise, thick bauxitic profiles later formed from weathering of 14 Ma to 23 Ma old trachyte and basalt are well preserved at altitudes of 1500 to 1800 m in the eastern Nigeria (Schwarz, 1997). With the mid-Miocene climatic optimum, Lateritic weathering intensified in Africa (e.g., Beauvais et al, 2008;De Putter and Ruffet, 2020), and more generally on continents of the inter-tropical belt (Retallack, 2010) even at relatively high altitudes, e.g., upon elevated continental margins (Jean et al, 2020), where transported-limited erosion regimes have potentially controlled landscapes evolution over the Cenozoic.…”
Section: Introductionmentioning
confidence: 96%
“…Given that tectonic movements are relatively slow, and the apparent increase in proto‐monsoon intensity at the Oligocene‐Miocene boundary in our records occurs over <500 kyr, it is likely that the sudden step‐change we observe in the eastern Arabian Sea at ∼23 Ma is primarily due to orbitally forced climatic factors superimposed on long‐term regional tectonic forcing of oceanic gateways and uplift. The strengthening of a proto‐SAM system by the earliest Neogene is supported by fossil megaflora in India (Srivastava et al., 2012), dust provenance studies from the Maldives (Betzler et al., 2016), enhanced weathering of the Western Ghats at the Oligocene‐Miocene boundary (Bonnet et al., 2016; Jean et al., 2020), a major Oligocene‐Miocene unconformity in the Himalayan foreland basin (Clift & Vanlaningham, 2010), increased erosion of the Himalayan foreland basin evidenced from thermochronology data (Clift et al., 2008; Webb et al., 2017), and increased SAM precipitation observed in a recent modeling study (Thomson et al., 2021). Data from the same Site NGHP‐01‐01A from the middle Miocene show a major strengthening in SAM precipitation and runoff from ∼15 Ma (Yang et al., 2020).…”
Section: Discussionmentioning
confidence: 99%
“…The Western Ghats are shown to be important drivers of orographic precipitation in this region, supplying runoff into the eastern Arabian Sea (Xie et al., 2006). A study of 40 Ar/ 39 Ar ages in the Western Ghats has shown that weathering and denudation has been active since at least the middle Eocene (∼44 Ma; Bonnet et al., 2016; Jean et al., 2020). Modeling studies suggest that African and Arabian topography impact the strength and pattern of the Somali Jet but with only small effects on the spatial pattern, strength and seasonality of SAM precipitation (Chakraborty et al., 2009; Wei & Bordoni, 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Paleosurfaces are preserved in the present-day landscape in most stable continental intraplate regions under humid and sub-humid tropical climate conditions as a result of slow denudation rate, relatively tectonic stability and stark lithological variability (e.g., Monteiro et al, 2014;. The remnants of the upper and older surfaces are covered by thick highly weathering profiles, including indurated horizons known as either Fe or Al duricrusts, which record the major weathering periods through time Mathian et al, 2019;Jean et al, 2019). Despite its formation and transformation processes have been extensively studied in the last sixty years (Maignien, 1958;Alexander and Cady, 1962;McFarlane, 1976;Beauvais and Tardy, 1993;Bitom and Volkoff, 1993 and references therein), the constraints of distinct weathering periods remain dispersed (e.g., Bonnet et al, 2016;Allard et al, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…Regarding the Brazilian territory, where its occurrence is widespread (~33%), Ferralsols are widely reported as occurring in the distinct landforms which are recognised by as Sul-Americana Surface (SAS; upper landform) supposedly from the Upper Cretaceous and Oligocene and Velhas Surface (VS; lower landform) supposedly from the Neogene Motta et al, 2002), although no geochronological data are widely available to support such age range. The upper landform and other analogous in the intertropical zone have been covered by thick highly and long-term weathered profiles including duricrusts, and distinct weathering periods have influenced its evolution Jean et al, 2019;Mathian et al, 2019;. However, there are still few studies that reveal the influence of these periods on the processes that operated or are currently underway in soils developed in ancient landscapes.…”
Section: Introductionmentioning
confidence: 99%